Group polarization in the team dictator game reconsidered - Wolfgang J. Luhan; Martin Kocher; Matthias Sutter (University of Innsbruck, Department of Public Finance, 2007)
While most papers on team decision-making find that teams behave more selfishly, less trustingly and less altruistically than individuals, Cason and Mui (1997) report that teams are more altruistic than individuals in a dictator game. Using a within-subjects design we re-examine group polarization by letting subjects make individual as well as team decisions in an experimental dictator game. In our experiment teams are more selfish than individuals, and the most selfish team member has the strongest influence on team decisions. Various explanations for the different findings in Cason and Mui (1997) and in our paper are discussed.
Keywords: C72; C91; C92; D70; 330; experiment; dictator game; team behavior; social preferences; Nichtkooperatives Spiel; Gruppenentscheidung; Diktatur; Eigeninteresse; Soziale Wohlfahrtsfunktion; Test; Theorie